Augmented Reality (Ar) In Learning Social Science (Ips) In Elementary Schools - Salmiyanti Salmiyanti; Yeni ERITA; Rati Syafiana PUTRI; NIVETIKEN NIVETIKEN (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
The Augmented Reality is an interactive medium, namely virtual images that are integrated into real life. The study employs literature review, especially by using secondary data obtained by summarizing several research articles related to the use of media which are carried out with the aim of describing and interpreting relevant information related to the use of augmented reality media. The study results are: 1) IPS learning in elementary schools is intended for students to become human beings and good citizens, as expected by themselves, their parents, society and religion; 2) Learning Media can make it easier for someone to convey a material or information to listeners; 3) AR media as a technology that objects in two or three dimensions in a certain way. AR media provides space for students to improve their learning process